Evaluation of PTGS2 Expression, PIK3CA Mutation, Aspirin Use and Colon Cancer Survival in a Population‐Based Cohort Study. Issue 4 (April 2017) - Gray, Ronan T; Cantwell, Marie M; Coleman, Helen G; Loughrey, Maurice B; Bankhead, Peter; McQuaid, Stephen; O'Neill, Roisin F; Arthur, Kenneth; Bingham, Victoria; McGready, Claire; Gavin, Anna T; Cardwell, Chris R; et al.
Abstract : OBJECTIVES: : The association between aspirin use and improved survival after colorectal cancer diagnosis may be more pronounced in tumors that have PIK3CA mutations or high PTGS2 expression. However, the evidence of a difference in association by biomarker status lacks consistency. In this population‐based colon cancer cohort study the interaction between these biomarkers, aspirin use, and survival was assessed. METHODS: : The cohort consisted of 740 stage II and III colon cancer patients diagnosed between 2004 and 2008. Aspirin use was determined through clinical note review. Tissue blocks were retrieved to determine immunohistochemical assessment of PTGS2 expression and the presence of PIK3CA mutations. Cox proportional hazards models were used to calculate hazard ratios (HR) and 95% confidence intervals (CI) for colorectal cancer‐specific and overall survival. RESULTS: : In this cohort aspirin use was associated with a 31% improvement in cancer‐specific survival compared to non‐use (adjusted HR=0.69, 95% CI 0.47–0.98). This effect was more pronounced in tumors with high PTGS2 expression (PTGS2‐high adjusted HR=0.55, 95% CI 0.32–0.96) compared to those with low PTGS2 expression (PTGS2‐low adjusted HR=1.19, 95% CI 0.68–2.07, P for interaction=0.09). The aspirin by PTGS2 interaction was significant for overall survival (PTGS2‐high adjusted HR=0.64, 95% CI 0.42–0.98 vs. PTGS2‐low adjusted HR=1.28, 95% CI 0.80–2.03, P for interaction=0.04). However, no interaction was observed between aspirin use and PIK3CA mutation status for colorectal cancer‐specific or overall survival. CONCLUSIONS: : Aspirin use was associated with improved survival outcomes in this population‐based cohort of colon cancer patients. This association differed according to PTGS2 expression but not PIK3CA mutation status. Limiting adjuvant aspirin trials to PIK3CA‐mutant colorectal cancer may be too restrictive.